Advances in computational approaches in biomechanics - Pain, Pritam, 1993-; Banerjee, Sreerup, 1981-; Bose, Goutam Kumar, 1970- (Advances in mechatronics and mechanical engineering (AMME) book series., 2022)
"This book gives an insight into the current trends of application of intelligent computational techniques used to analyze a multitude of phenomena in the field of biomechanics, offering a series of sophisticated techniques used for computer simulation in both solid mechanics, fluid mechanics and fluid-solid interface across different domain of biological world and across various dimensional scales along with relevant case studies"--